Evaluasi Usability Aplikasi MY JNE Dengan Metode User Experience Questionnaire (UEQ) Dan Heuristic Evaluation - Reinardus Dimas Bagus Kurniawan; Satrio Hadi Wijoyo; Niken Hendrakusma Wardani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
PT Jalur Nugraha Ekakurir (JNE) is a shipping service company to various regions in Indonesia and overseas. JNE is one of the options for sending goods in e-commerce. PT JNE has a mobile application that has features such as tracking items, checking rates, and a variety of other features. Based on observations and responses found in the Play Store, usability problems was found in the MY JNE application that had an impact on poor user experience. A new design recommendation can be proposed to reduce such problems. This study combines the UEQ (User Experience Questionnaire) method to obtain quantitative user experience from users and Heuristic Evaluation to obtain qualitative evaluations from evaluators. The first step is to find the level of user experience from the UEQ method and then continue with the Heuristic Evaluation to the evaluator on finding more problems. The next step is analyzing the results obtained and then draw conclusions by making design improvements. There were 30 individuals who participated in this study who were selected based on several criteria which are currently staying in Malang and own a MY JNE account. The UEQ benchmark measurement results in the Bad category for Attractiveness, Efficiency, Dependability, Stimulation, and Novelty. However, for the Perspicuity scale, it produces a Below Average category. The evaluator found 22 usability issues and suggested design improvements for the future. Consolidation has been carried out and followed by designing prototypes from evaluator recommendations. The prototype design that was built was based on 10 principles of usability Nielsen and Google Material Design. The results of testing the prototype have completed 22 previous usability problems and found a new problem with a minor severity ratings value.